Evolution Stages and Petrology of the Kekuknai Volcanic Massif as Reflecting the Magmatismin Backarc Zone of Kuril-Kamchatka Island Arc System. Part 1. Geological Position and Geochemistry of Volcanic Rocks - Koloskov A.V.; Flerov G.B.; Perepelov A.B.; Melekestsev I.V.; Puzankov M.Yu.; Filosofova T.M. (Journal of Volcanology and Seismology, 2011)
The evolution of the Quaternary Kekuknai volcanic massif (the western flank of the Sredinnyi Range in Kamchatka) has been subdivided into five stages: (I) the pre-caldera trachybasalt- basaltic andes- ite, (2) the extrusive trachyandesite-trachydacite, (3) the early trachybasalt, (4) the middle hawaiite- mugearite (with occasional occurrences of basaltic andesites), and (5) the late trachybasalt-hawaiite- mugearite (with occasional andesites) of areal volcanism. On the basis of petrologic data we identified the island arc and the intraplate geochemical types of rocks in the massif. The leading part in petrogenesis was played by dynamics of the fluid phase with a subordinated role of fractional crystallization and hybridism. Successive saturation of rocks with the fluid phase in the course of melt evolution stopped at the time of caldera generation when most fluid mobile elements and silica had been extracted. The geological and petrologic data attest to the formation of the massif in the environment of a backarc volcanic basin during the beginning of rifting with active participation of mantle plume components.